2021
DOI: 10.3390/genes12040536
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Revealed Ameliorative Effects of Bacillus Based Probiotic on Immunity, Gut Barrier System, and Metabolism of Chicken under an Experimentally Induced Eimeria tenella Infection

Abstract: In this study, we performed transcriptome analysis in the cecum tissues of negative control untreated non-challenged (NC), positive control untreated challenged (PC), and Bacillus subtilis (B. subtilis) fed challenged chickens (BS + ET) in order to examine the underlying potential therapeutic mechanisms of Bacillus based probiotic feeding under an experimental Eimeria tenella (E. tenella) infection. Our results for clinical parameters showed that birds in probiotic diet decreased the bloody diarrhea scores, oo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
(46 reference statements)
1
13
0
Order By: Relevance
“…Probiotics are microorganisms that are beneficial to the health of the host and stimulate the innate and adaptive immune systems [ 4 , 5 ]. Bacillus subtilis is one of the main sources of probiotics and is classified as GRAS (Generally Recognized as Safe) by the US Food and Drug Administration (FDA).…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics are microorganisms that are beneficial to the health of the host and stimulate the innate and adaptive immune systems [ 4 , 5 ]. Bacillus subtilis is one of the main sources of probiotics and is classified as GRAS (Generally Recognized as Safe) by the US Food and Drug Administration (FDA).…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that EtROP17 may play a crucial role in parasite replication within chicken intestinal epithelial cells. Moreover, the cell to ECM interaction can form physical barriers to prevent invasion of pathogens ( 35 ). This indicated that, besides affecting intestinal immune network for IgA production, EtROP17 may contribute to defense against microbial infections through affecting ECM-receptor interaction.…”
Section: Discussionmentioning
confidence: 99%
“…This study was enriched by blood transcriptomic analysis of changes in the expression of genes related to the TLR signaling pathway, response to interferon-β, tumor necrosis factor signaling pathway, systemic lupus erythematosus, and primary immunode ciency. TLRs are a type of PRR that recognize pathogenassociated molecular patterns (PAMPs) in different microorganisms and act as a bridge between the innate and adaptive immune systems (26), activating multiple signaling pathways in immune cells and thus, providing a defense mechanism against pathogens (5). TLR2-TLR1 or TLR2-TLR6 heterodimers recognize different pathogen-expressed PAMPs including lipoproteins, peptidoglycans and yeast glycans (27).…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics are microorganisms that are bene cial to the health of the host and stimulate the innate and adaptive immune systems (4,5). Bacillus subtilis is one of the main sources of probiotics and is classi ed as GRAS (Generally Recognized as Safe) by the US Food and Drug Administration (FDA).…”
Section: Introductionmentioning
confidence: 99%